The Aspartame diet: an investigation of consumer perceptions and consuption of diet Soda - King, Tayla Ann (The IIE, 2016)
find out whether or not the health risks of drinking diet soda may influence health-conscious women to rather drink alternative beverages. It is necessary to try and establish if these risks can and will influence the behaviour of health-conscious women and whether or not this will result in the selection of alternative beverages. I have researched particular themes which include; the relationship between female gender issues and dieting, the modern-day health-conscious woman and the food additive aspartame, therefore, highlighting the health risks that are associated with the consumption of this chemical. I have analysed primary and secondary data throughout this research process. My secondary research involved creating an archive for content analysis. The archive was filled with peer-reviewed articles, academic journals and novels. My primary research consisted of creating an online qualitative survey which was later analysed by a method of thematic analysis. This research will contribute towards highlighting the health-conscious woman's current perception of diet soda and the harmful risks that are associated with drinking the diet beverage. Regardless of the harmful chemicals that are found within this diet soda beverage, the majority of females would rather limit the amount of diet soda that they consume and therefore, continue to drink this beverage instead of giving up diet soda completely. A small percentage of women will chose to ignore the health risks and therefore, choose a chemical intake over a calorie intake. However, research suggests that there is a promising amount of these ‘health-conscious’ women that will chose an alternative beverage over diet soda, once they have been informed about the risks that are associated with this diet soda product.
Thesis
Keywords: Diet soda; Health-conscious; Aspartame; Health risks; Diet beverage